Trade and Harmonization : If Your Institutions are Good, Does it Matter if They are Different ? - Islam, Roumeen; Reshef, Ariell (World Bank, Washington, DC, 2012)
Good institutional quality (function) and similar institutional design (form) can promote international trade by reducing transactions costs. The authors evaluate the relative importance of function versus form in a gravity model, using an indicator of different legal systems as a proxy for differences in form, together with indicators of overall institutional quality. They find that good institutions promote trade much more than similar legal systems and have much more explanatory power. This effect is economically large-up to 10 times the effect of different legal systems. Moreover, better infrastructure matters as much as good institutions.